Perkembangan Lembaga Pendidikan Salafi dan Pengaruhnya terhadap Pendidikan di Indonesia - Afandi, Muhamad Ridwan; Rizqulloh, Muhammad Naufan (Universitas Muhammadiyah Prof Dr Hamka, 2025)
This study examines the development and influence of Salafi educational institutions in Indonesia on the national education system, particularly Islamic education. Employing a qualitative approach through literature review, the research traces the origins, classifications, and dissemination strategies of two major Salafi branches: Traditionalist and Reformist. The findings indicate that Salafi educational institutions have grown significantly since the 1980s, driven by financial support from Gulf countries and Middle Eastern alumni networks. Traditionalist Salafi institutions are generally exclusive, emphasizing a literalist-scriptural curriculum focused on Islamic creed (tauhid) while minimizing general education. In contrast, Reformist Salafis such as Muhammadiyah, Persis, and Al-Irsyad integrate religious teachings with modern science and general education. The impact of these institutions is ambivalent—while they offer a structured model of Islamic education, their rigid ideological stance may challenge national values of pluralism and tolerance.